Sensory Characteristics of Meat Sausage Products with Modified Cassava Flour as Filler - Surfiana Surfiana; Chandra Utami Wirawati; Dwi Eva Nirmagustina (Jurnal Penelitian Pendidikan IPA, 2024)
The use of modified cassava starch and flour in this study aims to obtain the optimal concentration of modified cassava starch and flour ratio in meat sausage emulsion type products and characterize organoleptic properties in meat sausage emulsion type products using modified cassava starch and flour as fillers. The ingredients used are modified cassava starch and flour, beef obtained from the Son Haji Sonny Bandar Lampung slaughterhouse, chicken meat from PT. Ciomas Adisatwa Lampung, sausage sleeves, and seasonings used in making beef sausages. The treatment given is a ratio of starch:modified cassava flour with a ratio of 90:10; 80:20; 70:30; and 60:40. The sensory test results showed that the most preferred sensory characteristics of sausages were sausages with a modified 80:20 starch:cassava flour ratio treatment for the sensory characteristics of sausage taste and texture. As for color sensory characteristics at a ratio of 60:40; and for aroma sensory characteristics at a ratio of 70:30. From the sensory characteristics that are closer to the quality characteristics of sausages are texture and taste, it can be concluded that the most preferred sausage is sausage with the addition of starch and modified cassava flour in a ratio of 80: 20.